Cost and value management in projects - Venkataraman, Ray R.; Pinto, Jeffrey K. (John Wiley & Sons, 2023)
Cost and Value Management in Projects Project manager's guide to achieving cost efficiency and value optimization--thoroughly updated with new cases, examples, and problem sets The newly revised and updated Second Edition of Cost and Value Management in Projects provides project managers with a thorough understanding of the various dimensions of cost and value in projects, along with the factors that impact them and the managerial approaches for achieving cost efficiency and value optimization. Whereas most cost management books discuss the topic from a tactical perspective, such as through the use of simple budgeting or Earned Value Analysis, this Second Edition addresses cost from a strategic perspective, examining project management decision areas that have the potential to enhance value and providing an integrated framework for managing cost. The Second Edition includes updates to key topic areas such as project benefits realization, updated end-of-chapter exercises such as discussion questions and problem sets, updated case studies, and new spreadsheet analytic techniques and examples. Written by two highly qualified authors with significant experience in the field, Cost and Value Management in Projects includes information on: Value management through value planning, engineering, and analysis from the perspective of projects, and best practices on how to avoid common pitfalls in managing cost and value Organization strategy and project selection, organization structure and culture, project definition (and contracts), and estimating project times and cost Developing project plans and schedules, managing risk, scheduling resources and cost, reducing project duration, leadership, performance measurement, and project closure Attainment of value in complex environmental settings and benefits of effective project management Cost and Value Management in Projects is an essential resource on the subject for stakeholders at all corporate and government levels, including executives measuring performance, middle level corporate managers, project and team managers, engineers, project team members, and business consultants, along with students in related programs of study.